Pathogen elimination by probiotic Bacillus via signalling interference. (25th October 2018) - Piewngam, Pipat; Zheng, Yue; Nguyen, Thuan; Dickey, Seth; Joo, Hwang-Soo; Villaruz, Amer; Glose, Kyle; Fisher, Emilie; Hunt, Rachelle; Li, Barry; Chiou, Janice; Pharkjaksu, Sujiraphong; et al.
Abstract Probiotic nutrition is frequently claimed to improve human health. In particular, live probiotic bacteria obtained with food are thought to reduce intestinal colonization by pathogens, and thus to reduce susceptibility to infection. However, the mechanisms that underlie these effects remain poorly understood. Here we report that the consumption of probioticBacillus bacteria comprehensively abolished colonization by the dangerous pathogenStaphylococcus aureus in a rural Thai population. We show that a widespread class ofBacillus lipopeptides, the fengycins, eliminatesS .aureus by inhibitingS .aureus quorum sensing—a process through which bacteria respond to their population density by altering gene regulation. Our study presents a detailed molecular mechanism that underlines the importance of probiotic nutrition in reducing infectious disease. We also provide evidence that supports the biological significance of probiotic bacterial interference in humans, and show that such interference can be achieved by blocking a pathogen's signalling system. Furthermore, our findings suggest a probiotic-based method forS .aureus decolonization and new ways to fightS .aureus infections. Lipopeptides secreted byBacillus bacteria block quorum sensing byStaphylococcus aureus and thereby inhibit the growth of this opportunistic pathogen in the gut, suggesting why people in rural Thailand who are colonized byBacillus are not also colonized byS .aureus .